Response of Growth and Yield of Mustard Toward Gibberellin on Peat Soil - ASMADI, ASMADI (Fakultas Pertanian Universitas Tanjungpura, 2021)
The increase in market demand for mustard needs to be balanced with an increase in production, one of which is by utilizing peat land which is balanced with the provision of gibberellin as a plant growth regulating hormone. This study aims to determine the best concentration of gibberellin (GA3) in increasing the growth and yield of mustard on peat soil. The research was conducted at West Kalimantan Province, Southeast Pontianak Sub-district. The research was conducted from September 12nd